ЗМІНИ КАНОНІЧНОГО СТАТУСУ ПРАВОСЛАВНОЇ ЦЕРКВИ В УКРАЇНІ (1918ñ1930-ті рр.): ВІД АВТОНОМІЇ ДО ЕКЗАРХАТУ (Zaporizhzhia Historical Review, 2021)
The changes of the canonical status of the Orthodox Church in Ukraine during 1918ñ1930 were analyzed. They have been reviewed as the result of the confrontation of the modernizational processes that took place in the social and cultural, the state and the church life. The plot and the sources of the transformation of the autonomous Ukrainian Orthodox Church in the exarchate and the specialty of the savage of such status were reconstructed.